Pengaruh Profitabilitas dan Leverage Terhadap Tax Avoidance (Studi Kasus Pada Perusahaan Food And Beverage) - Widya Dwi Agustin; Asep Muslihat (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The Food and Beverage sector is thriving in Indonesia due to companies leveraging the diverse natural resources the country possesses. As a result of this opportunity, many entrepreneurs are keen on establishing businesses that utilize these resources. Naturally, in building a company, there is always the expectation of achieving high profitability or significant profits, and it is hoped that the company's liabilities do not exceed what is necessary. Thus, the purpose of this research is to determine the influence of the variables of profitability (return on assets) and leverage (debt to asset ratio and debt to equity ratio) on tax avoidance in manufacturing companies in the food and beverage subsector during the period 2018 – 2022. Based on the research, it was found that the return on equity variable has a significant negative effect on the tax avoidance variable, while the debt to asset ratio and debt to equity ratio variables do not have a significant effect on the tax avoidance variable. However, when tested simultaneously, the results showed that the profitability and leverage variables have a significant effect on tax avoidance.